Η μεσοπολεμική πεζογραφία. Τόμος 1ος : από τον πρώτο ως τον δεύτερο παγκόσμιο πόλεμο 1914-1939 (Σοκόλης, 1996)
Ξενόπουλος Γρηγόρης -- Χατζόπουλος Κ. -- Δημοσθένης Βουτηράς -- Χάρης Πέτρου -- Πολ. Παπαχριστοδούλου -- Ζαχαρίας Παπαντωνίου -- Πικρός Πέτρος -- Στρατής Δούκας -- Κατηφόρης -- Στρατής Μυριηβήλης -- Λεβάντας Χρήστος -- Στέλιος Ξεφλούδας -- Αγγελος Δόξας -- Αγγελος Τερζάκης -- Θανάσης Πετσάλης -- Παπαδιαμάντης -- Διονύσιος Κόκκινος -- Πέτρος Σπανδωνίδης -- Αλκ. Γιαννόπουλος -- Γιώργος Θεοτοκάς -- Γιώργος Δέλιος